Analyzing Serum Uric Acid Levels in Essential Hypertension with Focus on Age and BMI: A Study from a Tertiary Care Center in India” - VERMA, DR RAJEEV; Singh, Dr. Sandeep Kumar; VERMA, Dr. Manisha; Meena, Dr. Mahendra Kumar; Mukherjee, Dr. Anirudh; Kumar, Dr. Pramod; Sharma, Dr. Manu (International Journal of Innovative Research in Medical Science, 2024)
This study outlines a comprehensive approach to exploring the interplay between serum uric acid levels, age, and BMI in hypertensive patients, aiming to provide actionable insights and contribute to the broader scientific understanding of these relationships. To fulfill this objective, a study at tertiary-care teaching hospital, Northern India (June 2017 - December 2018) involved 145 hypertensive patients and 145 matched controls, using a case-control, cross-sectional design. Participants were randomly selected and included those over 12 years old with hypertension per JNC 7/8 criteria, excluding individuals with severe hypertension, recent myocardial infarction, major infections, chronic diseases, or those on specific drugs affecting uric acid. Smokers and heavy drinkers were also excluded. Data collection included informed consent, venipuncture, history, physical exams, and tests such as blood pressure, serum uric acid, BMI, and various blood tests. Statistical analysis was performed with mean, standard deviation, t-tests, and Pearson's correlation, with significance set at p < 0.05. The study reveals a balanced age distribution with most participants over 40 years, and consistent blood pressure categories across cases and controls, with cases showing higher rates of hypertension. Cases also exhibit significantly higher average blood pressure levels. Weight categories are similarly distributed between cases and controls, with a trend towards higher SUA levels in individuals with higher BMI. A strong positive correlation is observed between SUA levels and both systolic and diastolic blood pressure. Males show a slightly higher prevalence of hypertension compared to females, reflecting a greater overall burden of the condition. The study concludes that elevated SUA levels are significantly correlated with higher blood pressure, both systolic and diastolic. The analysis reveals that hypertensive cases exhibit higher average blood pressure levels and a trend towards increased SUA levels with higher BMI. Additionally, males show a slightly greater prevalence of hypertension compared to females. These findings underscore the importance of monitoring SUA levels and BMI in managing hypertension and suggest that interventions targeting these factors could be beneficial in reducing cardiovascular risk.